2017
DOI: 10.1093/mnras/stx3033
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in the production of p nuclides in thermonuclear supernovae determined by Monte Carlo variations

Abstract: Thermonuclear supernovae originating from the explosion of a white dwarf accreting mass from a companion star have been suggested as a site for the production of p nuclides. Such nuclei are produced during the explosion, in layers enriched with seed nuclei coming from prior strong s processing. These seeds are transformed into protonricher isotopes mainly by photodisintegration reactions. Several thousand trajectories from a 2D explosion model were used in a Monte Carlo approach. Temperaturedependent uncertain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 42 publications
0
51
0
Order By: Relevance
“…From Eqs. (5) and (6), the following properties of the reactions under study can be expected. The total reaction cross section σ reac (summed over all non-elastic channels) depends only on the transmission T α,0 in the entrance channel and is thus only sensitive to the chosen α-nucleus optical model potential (A-OMP).…”
Section: A Formalism and General Remarksmentioning
confidence: 99%
“…From Eqs. (5) and (6), the following properties of the reactions under study can be expected. The total reaction cross section σ reac (summed over all non-elastic channels) depends only on the transmission T α,0 in the entrance channel and is thus only sensitive to the chosen α-nucleus optical model potential (A-OMP).…”
Section: A Formalism and General Remarksmentioning
confidence: 99%
“…3. The standard rate set and the assigned uncertainties were the same as previously used in our works (Rauscher et al 2016;Nishimura et al 2017Nishimura et al , 2018Cescutti et al 2018): rates for neutron-, proton-, and α-induced reactions were a combination of theoretical values by Rauscher & Thielemann (2000), supplemented by experimental rates taken from Dillmann et al (2006) and Cyburt et al (2010). Decays and electron captures were taken from a REACLIB file compiled by Freiburghaus & Rauscher (1999) and supplemented by rates from Takahashi & Yokoi (1987) and Goriely (1999) as provided by Aikawa et al (2005) and Xu et al (2013).…”
Section: Nucleosynthesis With Monte Carlo Variationsmentioning
confidence: 99%
“…Therefore, it is critical to identify the key photodisintegration reactions in the pprocess nucleosynthesis, especially the (γ,p) and (γ,α) reactions, that need prioritizing for the experimentally study. Recently, the uncertainties of the p-nuclei production originated by the variations of the astrophysical reaction rates are systematically studied, using the state-of-the-art Monte Carlo procedure [11,12], and the important reactions for determining the abundance of the p-nuclei are identified. In the present study, the key reactions of (γ,p) and (γ,α) identified by Refs.…”
Section: Proposed Photonuclear Experimentsmentioning
confidence: 99%
“…In the present study, the key reactions of (γ,p) and (γ,α) identified by Refs. [11,12] are initially considered as the candidates of the photonuclear measurement. Furthermore, by explicitly checking the half-live of the nuclei involved in these candidate reactions, it is found that many of them cannot be experimentally studied via the photonuclear channel, due to the unavailability of the radiative targets.…”
Section: Proposed Photonuclear Experimentsmentioning
confidence: 99%